High fat and/or high salt intake during pregnancy alters maternal meta‐inflammation and offspring growth and metabolic profiles. Issue 8 (5th August 2014) - Reynolds, Clare M.; Vickers, Mark H.; Harrison, Claudia J.; Segovia, Stephanie A.; Gray, Clint
Abstract A high intake of fat or salt during pregnancy perturbs placental function, alters fetal development, and predisposes offspring to metabolic disease in adult life. Despite its relevance to modern dietary habits, the developmental programming effects of excessive maternal fat and salt, fed in combination, have not been examined. We investigated the effects of moderately high maternal fat and/or salt intake on maternal metainflammation and its consequences on fetal and weanling growth and metabolic profile. Female Sprague–Dawley rats were fed a standard control diet (CD), 4% salt diet (SD), 45% fat diet (HF) or 4% salt/45% fat combined diet (HFSD) 3 weeks prior to and throughout pregnancy and lactation. Plasma and tissue samples were collected at day 18 of pregnancy from mother and fetus, and at postnatal day 24 in weanlings. Markers of adipose tissue inflammation, macrophage infiltration, lipogenesis, nutrient transport, and storage were altered in pregnant dams receiving high‐fat and/or ‐salt diets. This was accompanied by increased fat mass in high‐fat groups and differential hepatic lipid and glucose homeostasis. Offspring of high fat‐fed mothers had reduced fetal weight, displayed catch‐up growth, increased fat mass, and altered metabolic profiles at weaning. Maternal diets high in fat and/or salt affect maternal metabolic parameters, fetal growth and development, metabolic status, and adipoinsular axis in the weanling. Results presented here highlight the importance of diet in expectant mothers or women considering pregnancy. Furthermore, the potential for maternal nutritional intervention strategies may be employed to modify the metabolic disease risk in adult offspring during later life.